GATE CSE
First time here? Checkout the FAQ!
x
+3 votes
72 views

find the solution of the recurence relation

a=3an-1 + 2n  initial conditon is given as a1=3 ?

asked in Mathematical Logic by Active (1.3k points) 1 2 16 | 72 views

2 Answers

+3 votes
Best answer

Your question is of the form non linear homogeneous solution with constant coefficient. 

so 

$a_{n}=a^{\left(h\right)}_{n}+a^{\left(p\right)}_{n}$

where ,$\text{h=Homogeneous  and p= polynomial}$

 

$\text{solve  }   \rightarrow a^{\left(h\right)}_{n}$

characteristics equation will be 

$r=3 \Rightarrow root=3$

so,$a^{\left(h\right)}_{n}=\alpha *3^{n}$

now solve $ P_{n}=a^{\left(p\right)}_{n}$

Let $Q_{n}  \: \text{be our trial equation },Q_{n}=cn+d$

Then our equation 

$a_{n}=3*a_{n-1}+2  \: \text{becomes} \left ( c*n+d \right )=3*\left ( c*\left ( n-1 \right )*d \right )$

$\Rightarrow 2cn+2n+2d-3c=0$

$\Rightarrow n \left (2c+2\right )+2d-3c=0$

solving/comparing both sides,

$c=-1,d= - \frac {3}{2}$

 

Now assemble all things you obtained.

$a_{n}=a^{\left(h\right)}_{n}+a^{\left(p\right)}_{n}$

$a_{n}=\alpha *3^{n}+\left ( cn+d \right )$

$a_{n}=\alpha *3^{n}-n-\frac{3}{2}$

put value of $a_{1}=3,3=\alpha *3^{1}-1-\frac{3}{2},\alpha =\frac{11}{6}$

$a_{n}=\frac{11}{6} *3^{n}-n-\frac{3}{2} \text{is your answer}$

answered by Veteran (13.7k points) 16 55 115
selected by
why u take particular solution as : cn+d

for poylnomials of first degree take 

n=Cn+d

n^2=Cn^2+bn+a.

2^n=A.2^n.

+4 votes

It is non homogeneous solution.so first find homogenous and find particular solution..

$a_{n}-3a_{n-1}$=2n.---------------------(i)

Case I) finding homogeneous part.

i.e)$a_{n}-3a_{n-1}$=0.

t-3=0

t=3.(it is root)

Solution is $a_{n}$=p.$3^{n}$.

Case II) finding non homogeneous part.

Non homogenneous part is polynomial so $a_{n}$=An+b.$-----------(ii) sub this equation in (i)

Then(An+c)-3(A(n-1)+c)=2n

n(-2A)+3A-2c=2n.

compare both sides then A=-1 and c=-3/2.

particular solution is=Homogeneous +non homogeneous .

$a_{n}=p.3^{n}-n-3/2.$.

Given that a1=3.

then 3=3p-1-3/2.

p=11/6.

substitute in above equation $a_{n}=[11/6].3^{n}-n-3/2.$

answered by Veteran (11.6k points) 6 20 88

Related questions

+3 votes
1 answer
1
+1 vote
1 answer
2
asked in Mathematical Logic by Pavan Kumar Munnam Veteran (10.6k points) 7 17 54 | 72 views


Quick search syntax
tags tag:apple
author user:martin
title title:apple
content content:apple
exclude -tag:apple
force match +apple
views views:100
score score:10
answers answers:2
is accepted isaccepted:true
is closed isclosed:true
Top Users Oct 2017
  1. Arjun

    23684 Points

  2. Bikram

    17288 Points

  3. Habibkhan

    9194 Points

  4. srestha

    6486 Points

  5. Debashish Deka

    5478 Points

  6. jothee

    5168 Points

  7. Sachin Mittal 1

    4910 Points

  8. joshi_nitish

    4504 Points

  9. sushmita

    4078 Points

  10. Rishi yadav

    3998 Points


Recent Badges

Nice Comment Pooja Palod
Famous Question Harsh181996
Verified Human ASK
Good Comment Bikram
Good Comment Arjun
Nice Comment Arjun
Famous Question Meenakshi Sharma
Famous Question Meenakshi Sharma
Nice Question smartmeet
Nice Comment Vicky rix
27,426 questions
35,275 answers
84,602 comments
33,523 users